Analisis Parkir di Toko Bintang Denpasar - I Made Kariyana (Jurnal Syntax Admiration, 2024)
In this digital era, smartphones have become very common among people around the world, where smartphones are often used as a communication tool that can help us communicate. Developments will continue to occur following the times that make the industry launch the latest products that come with complementary accessories that attract interest from consumers. With many industries launching the latest products. In addition, the industry also competes to distribute its products at affordable prices for the community. Toko Bintang Gatsu is a smartphone accessory and service store with quite affordable prices so that it is often visited by the surrounding community, which is located on Jl. Gatot Subroto Timur, No. 250, Tonja, North Denpasar District, Denpasar City. This Bintang store has quite a lot of consumers which causes the parking lot in the store to sometimes exceed capacity. In addition, the cause of excess parking capacity in the area is also influenced by the consumers of the swimming studio which is right next to the store. They collaborate with BSS Parking Company, which is engaged in parking management. The methods used in this analysis include observation or direct surveys in the field. The results showed that the capacity of the parking space at the location of the gatsu star store was that the capacity of two-wheeled vehicles exceeded from 08.45-10.15 and sometimes from 17.45-20.45 exceeded and according to the time interval, while for light vehicles began to exceed the capacity from 10.00-10.30 and also at 15.45-17.45